AN ANALYSIS OF STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT AT THE SECOND GRADE OF MTS-TI BATU BELAH - Fatma Asriani; Masrul Masrul (Journal of English Language and Education, 2018)
The objective of the research is to describe how the students’ reading comprehension of descriptive text. This research was conducted at MTS-TI Batu Belah. The subject of this research consists of 26 students of the second grade. The method of this research is a descriptive research. The researcher used two instruments, test and questionnaire. Based on the data analysis, it showed that the average of the students’ achievement in reading comprehension of descriptive text was 49. It was categorized in Poor level. Furthermore, the students’ responses showed that 21 the students like reading. Meanwhile, 5 the students didn’t like reading english text. 21 the students want to learne about new vocabulary before used dictionary. Meanwhile, 5 the students didn’t understand about the vocabulary without used dictionary. 16 the students can finding specific information. Meanwhile, 10 the students felt difficult in understand English well. 13 the students felt easy to find the main idea and the supporting detail. Meanwhile, 13 the students feel difficult to find the main idea . 16 the students felt didn’t difficult in guessing the title of the text. Meanwhile, 10 the students felt the title was difficult to guess. 12 the students felt didn’t like to answer the questions about vocabulary. Meanwhile, 14 the students felt the questions were difficult